A formação do Embu no período colonial: intersecção entre a ação evangelizadora dos jesuítas no âmbito da política colonial e as decorrências simbólicas e culturais do encontro de missionários e indígenas - Martins, Ivan Barbosa (2007)
The process of settling of Brazil IF gave Portugal after to consist as Kingdom and transforming into maritime country, searched the interests of the classrooms noble and members of the Church Catholic, transforming into a national Project with commercial impulses ando f religious mission. The entailing enters the Company of Jesus and Portugal is fact that if structure, then after its foundation for Inácio de Loyola, the Jesuits formed a religious corporation destined to constituent of the elite military service to be used in the Against-Reformation, in the fight in favor of the religion undertaken for the Pope. The sprouting of the Embu (M Boy), is atrelado in this interest, therefore we make na analvsis of the process f itssprouting. We search to understandthe paper of the missionaries, how much the ideal of the faith and the catequista settling, that the activity of the Company evidences, and the strategies articulated in promoting its facts to keep the cultural monopoly and to lead the sheep. The meeting between Jesuits and aboriginalds, was to sth by expectations and dicoveries in relation to the cultural process of universes that divergiam and ressignificavam, but that it was necessary for the social maintenance. The resulto of this meeting was, a popular religiousing marketing by a revealed religious sincretismo through religious parties. Therefore, the research object is the formation of Embu, city of the region metropolitan of São Paulo. We search the jesuítica action and the process of catequização of the guarani, and the cultural relations resultant of a religious ressignificação that resulted in the society of Embu a typically popular catolicismo. I Will be analyzing the colonial period, specifically that referring of São Paulo, even enter 1554 for 1700 return, in which if it consolidates the paper of the Pe. Belchior Pontes, then considered the founder of this city